2006
DOI: 10.1590/s1516-89132006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Use of smoking to add value to the salmoned trout

Abstract: The objective of this study was to make a comparison between the characteristics of salmoned trout (Salmo truta) and salmon (Salmo salar)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
6
12
0
Order By: Relevance
“…These findings is in line with Salan et al who report that during fish smoking and sun drying fish losses its moisture content, which result in increase in the concentration of nutrient in the remaining mass of fats [31].…”
Section: Resultssupporting
confidence: 91%
“…These findings is in line with Salan et al who report that during fish smoking and sun drying fish losses its moisture content, which result in increase in the concentration of nutrient in the remaining mass of fats [31].…”
Section: Resultssupporting
confidence: 91%
“…Salting induced a significant MC and PC increases, however smoking significantly (P < 0.05) reduced such counts. Our results are in agreement with other authors ( [39], [40]; [41]; [42]) who reported that smoking significantly (p˂0.05) reduced the total aerobic count to values much lower than that found in the corresponding fresh fish products. Such results are due to the antimicrobial effect of smoke polyphenols.…”
Section: Microbiological Analysissupporting
confidence: 94%
“…Similarly, Fapohunda and Ogunkoya (2006) reported that smoke drying methods increased the protein, ash and fat contents of C. gariepinus. Salan, Juliana and Marilia (2006) observed decrease of moisture, carbohydrate, lipid, potassium and vitamin C contents and increase of protein, ash, crude fibre, phosphorus and iron contents in smoked C. gariepinus. The authors further noted that the increase in the ash content in the smoked fish was due to the loss of humidity and that the significant reduction in the moisture content when the fish was smoked was as a result of the loss in moisture during hot smoking.…”
Section: Resultsmentioning
confidence: 73%